2021
DOI: 10.1016/j.ekir.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 trial Design of the Hepatocyte Growth Factor Mimetic ANG-3777 in Renal Transplant Recipients With Delayed Graft Function

Abstract: Introduction One-third of kidney transplantation patients experience acute kidney injury (AKI) resulting in delayed graft function (DGF), associated with increased risk of graft failure and mortality. Preclinical and phase 2 data indicate that treatment with ANG-3777 (formerly BB3), a hepatocyte growth factor (HGF) mimetic, may improve long-term kidney function and reduce health care resource use and cost, but these data require validation in a phase 3 randomized controlled trial. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this regard, longer-term changes in the eGFR might be considered as an end point in clinical trials. 43 An approach for pragmatic trials with very large sample sizes to consider is to have two coprimary end points, and these may be a combination of superiority in a nonmortality outcome and noninferiority in mortality.…”
Section: The Importance Of the Primary End Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, longer-term changes in the eGFR might be considered as an end point in clinical trials. 43 An approach for pragmatic trials with very large sample sizes to consider is to have two coprimary end points, and these may be a combination of superiority in a nonmortality outcome and noninferiority in mortality.…”
Section: The Importance Of the Primary End Pointmentioning
confidence: 99%
“…There may also be room for investigation of potential intermediate or surrogate outcomes, such as renal recovery and the risk of progression toward CKD. In this regard, longer-term changes in the eGFR might be considered as an end point in clinical trials 43 . An approach for pragmatic trials with very large sample sizes to consider is to have two coprimary end points, and these may be a combination of superiority in a nonmortality outcome and noninferiority in mortality.…”
Section: The Importance Of the Primary End Pointmentioning
confidence: 99%
“…HGF is nephro-protective in animal models of AKI, and recent studies have explored the effects of BB3/ ANG3777, a small molecule with strong HGF-like activity, which, when administered at 24 h after kidney ischemia in rats, improved survival and kidney function. BB3/ANG3777 is currently being tested in human AKI [18]. Human trials with recombinant IGF-1 have not demonstrated a beneficial effect.…”
Section: Alterations In Tubule Cell Proliferationmentioning
confidence: 99%
“…In a randomized, placebo-controlled phase 2 trial on oliguric patients after kidney transplantation, patients treated with ANG-3777 had a larger increase in urine output, a greater reduction in C reactive protein and neutrophil gelatinase-associated lipocalin and a higher estimated glomerular filtration rate (eGFR)[ 24 ]. More recently, Vincenti et al [ 25 ] started the Graft Improvement Following Transplant (GIFT) trial, which is a phase 3 trial on the hepatocyte growth factor mimetic ANG-3777 in kidney transplant recipients with DGF. The aim of GIFT is to generate data to advance the treatment of DGF.…”
Section: Therapy For Dgfmentioning
confidence: 99%